2014
DOI: 10.1242/jeb.103549
|View full text |Cite
|
Sign up to set email alerts
|

Niche-specific cognitive strategies: object memory interferes with spatial memory in the predatory bat, Myotis nattereri

Abstract: Related species with different diets are predicted to rely on different cognitive strategies: those best suited for locating available and appropriate foods. Here we tested two predictions of the nichespecific cognitive strategies hypothesis in bats, which suggests that predatory species should rely more on object memory than on spatial memory for finding food and that the opposite is true of frugivorous and nectivorous species. Specifically, we predicted that: (1) predatory bats would readily learn to associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
(77 reference statements)
1
11
1
Order By: Relevance
“…Based on acoustic tomography representations of prey resting on substrate, Clare and Holderied (2015) proposed that bats perceive changes in the depth profile and acoustic shadows cast by prey, especially when the surface ensonified is smooth (detection would be more difficult for cluttered surfaces, where prey might be concealed acoustically). Echolocation may also be used by gleaners to recognize the shape of specific plant species that are likely to host prey (Siemers 2001;Hulgard and Ratcliffe 2014).…”
Section: Echolocation Behaviour and Call Structurementioning
confidence: 99%
“…Based on acoustic tomography representations of prey resting on substrate, Clare and Holderied (2015) proposed that bats perceive changes in the depth profile and acoustic shadows cast by prey, especially when the surface ensonified is smooth (detection would be more difficult for cluttered surfaces, where prey might be concealed acoustically). Echolocation may also be used by gleaners to recognize the shape of specific plant species that are likely to host prey (Siemers 2001;Hulgard and Ratcliffe 2014).…”
Section: Echolocation Behaviour and Call Structurementioning
confidence: 99%
“…When tested in a twochoice task with a novel feeder of a different shape, these bats flew repeatedly to the trained round-shaped feeder, even though it was empty. Furthermore, Hulgard and Ratcliffe (2014) reported that object feature learning can inhibit later spatial location learning in M. nattereri. In our study, the insectivorous big brown bat (E. fuscus) learned to use the features of a landmark to guide its navigation, despite the changing landmark position across trials.…”
Section: Discussionmentioning
confidence: 99%
“…When tested in cue-conflicting conditions with no reward, both nectarivorous and frugivorous bat species preferred to visit the feeder consistent with the spatial cues (Carter et al, 2010;Thiele and Winter, 2005). By contrast, studies of insectivorous species (Myotis nattereri), which normally chase moving prey, showed that bats can rely on feature cues to locate food (Hulgard and Ratcliffe, 2014;Siemers, 2001). Siemers (2001) trained gleaning bats (Myotis nattereri) to feed in a round-shaped feeder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hierarchical use of spatial memory over associative learning has also been observed in the foraging behavior of nectar-feeding animals such as carpenter bees (Orth and Waddington 1997), hummingbirds (Hurly and Healy 1996) and bats (Thiele and Winter 2005;Stich and Winter 2006;Carter et al 2010) whose foraging resources are also relatively predictable in space and time. On the contrary, animals preying on unpredictable resources (e.g., swarms of insects) rely more on associative learning than on spatial memory to localize known resources (Hulgard and Ratcliffe 2014).…”
Section: Do Bats Make Hierarchical Use Of Cues?mentioning
confidence: 99%